2011
DOI: 10.1590/s0102-695x2011005000050
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of natural compounds of Stachytarpheta cayennensis (Rich.) Vahl, Verbenaceae, by scavenger of mitochondrial reactive oxygen species

Abstract: Abstract:The etiology of a range of diseases is associated with an excessive generation of reactive oxygen species (ROS). Exacerbated ROS production leads to mitochondrial dysfunction, cellular damage and apoptosis. Nowadays, many strategies are being developed for the targeted delivery of antioxidants compounds to mitochondria, trying to minimize the damages. Production of ROS was investigated by the molecular probes CM-H 2 DCFDA and Amplex Red. The purpose of this work is to evaluate the antioxidant capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Antonisamy et al presented a study with a pentacyclic triterpene isolated from Azimate tracantha (Salvadoraceae) that demonstrated an anti-inflammatory, analgesic, and antipyretic effect in mouse and rat models [3]. Montanha et al demonstrated this effect from the Loranthus regularis (Loranthaceae) extract and identified the phenolic constituents in this material [15], while Magalhães et al and Souza et al described antioxidant properties from Maytenus salicifolia (Celastraceae) and Stachytarpheta cayennensis (Verbenaceae) extracts [13,14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antonisamy et al presented a study with a pentacyclic triterpene isolated from Azimate tracantha (Salvadoraceae) that demonstrated an anti-inflammatory, analgesic, and antipyretic effect in mouse and rat models [3]. Montanha et al demonstrated this effect from the Loranthus regularis (Loranthaceae) extract and identified the phenolic constituents in this material [15], while Magalhães et al and Souza et al described antioxidant properties from Maytenus salicifolia (Celastraceae) and Stachytarpheta cayennensis (Verbenaceae) extracts [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, compounds such as proteases [11] and lectin were found to have hemagglutination inhibition [12]. The literature states that terpenes and phenolic compounds are commonly found in the genus Synadenium [8,9] and that these compounds present free radical inhibition and anti-inflammatory activities [3,13,14]. The aim of this work was to evaluate the antioxidant and anti-inflammatory activities as well as to perform a phytochemical investigation of the stem bark of S. grantii in order to identify the compounds responsible for its ethnopharmacological indications.…”
Section: Abbreviationsmentioning
confidence: 99%
“…However, pre-treatment of TBS-7 or MS-2 significantly minimised CCl 4 induced depletion of antioxidant and prevented lipid peroxidation. These results are attributable to the significant antioxidant and free radical scavenging potential of TBS-7 and MS-2 (de Souza et al, 2011;Zheng et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…NCs have various beneficial effects on human health (Lobo, Patil, Phatak, & Chandra, 2010). They play important roles as ROS scavenger (Rezaee et al, 2013(Rezaee et al, , 2014Souza et al, 2011), and exert antioxidative (Kim, Kim, Kim, & Heo, 1997), and anti-inflammatory (Dvořák, Vrzal, Maurel, & Ulrichová, 2006) activities in various tissues.…”
Section: Ncs That Protected Against Dox-induced Cardiotoxicity Via mentioning
confidence: 99%